1994
DOI: 10.1007/bf03160088
|View full text |Cite
|
Sign up to set email alerts
|

Aging modulates calcium-dependent phosphatidylinositol degradation by cerebral cortex synaptic plasma membrane phospholipases

Abstract: The synaptic plasma membrane (SPM) and cytosol fractions from cerebral cortex of adult (4-mo-old) and aged (27-mo-old) rats were used as a source of phospholipase A2 (PLA2) and phospholipase C (PLC). The activity of PLC acting on [3H-inositol]phosphatidylinositol ([3H]PtdIns) was investigated in the presence of endogenous and 2 mM Ca2+. Arachidonic acid (AA) release was studied in the same conditions, using 1-stearoyl-[2-14C]arachidonyl-sn-glycerophosphoinositol ([14C]PtdIns) as a substrate. In the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Enhanced PLA 2 activity, and/or up-regulation of specific PLA 2 isoforms, is observed in the aging brain and well correlates with neuronal degeneration and accelerated senescence [37,38]. The same is observed in hypoxic myocardial cells [24] as well as in models of hypoxia in the lung [25], brain [26] and kidney [27].…”
Section: The Cross-talk Between No and Arachidonic Acid In The Contexmentioning
confidence: 83%
“…Enhanced PLA 2 activity, and/or up-regulation of specific PLA 2 isoforms, is observed in the aging brain and well correlates with neuronal degeneration and accelerated senescence [37,38]. The same is observed in hypoxic myocardial cells [24] as well as in models of hypoxia in the lung [25], brain [26] and kidney [27].…”
Section: The Cross-talk Between No and Arachidonic Acid In The Contexmentioning
confidence: 83%
“…We demonstrated that enzyme activities involved in alternative pathways for phospholipid synthesis, such as PLD, are modi®ed by the effect of aging in different brain areas (Ilincheta de Boschero et al, 2000). PLC and PLA 2 enzymes bound to aged synap-tosomal membranes show higher activity than in adult membranes (Strosznajder et al, 1994). The formation and accumulation of very potent lipid messengers such as DAG, lysophospholipids and arachidonic acid in neurotransmission processes may play a role in the deterioration of neuronal function during aging.…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, the number of glutamate binding sites increases with age . Several alterations of biochemical events that take place during aging may inhibit GABAergic function in brain, such as a decreased cytoplasmic level of free Ca", activation of phospholipase AZ, enhancement of arachidonic acid (AA) and diacylglycerol (DAG) release, and gen-eration of oxygen radicals (Schwartz and Mindlin, 1988;Samochocki and Strosznajder, 1993;Strosznajder et al, 1994).…”
Section: Marek Samochocki and Joanna Strosznajdermentioning
confidence: 99%